Best evidence topic: Should ventral hernia repair be performed at the same time as bariatric surgery?. (November 2016) - Sait, Mohammed Saif; Som, Robin; Borg, Cynthia Michelle; Chang, Avril; Ramar, Sasindran
Abstract: A best evidence topic has been constructed using a described protocol. The three-part question addressed was: In morbidly obese patients undergoing bariatric surgery, when a ventral hernia is picked up in clinic or intraoperatively is concurrent repair of the hernia better than delayed repair after weight loss with regards to complication rates? Using the reported search, 179 papers were found. 5 studies were deemed to be suitable to answer the question. All 5 studies assessed were non randomised studies either retrospective or prospective and the overall quality of these studies was poor. The outcomes assessed were incidence of complications associated with hernia repair (recurrence, infection) and deferral of repair (small bowel obstruction). The patient's symptoms and anatomy is important in determining the timing of repair. The evidence does not provide a consensus for the optimal timing of ventral hernia repair for patients undergoing bariatric surgery, with some of the selected studies contradicting each other. However, the studies do affirm the risk of small bowel obstruction if hernias are left alone. The reported rate of surgical site infection is low when mesh repair is performed at the same time as weight loss surgery. Until large volume, high quality randomized control trials can be performed, a case by case approach is best, where the patients' symptoms, anatomy, type of bariatric surgery and their personal preferences are considered, and an open discussion on the risks and benefits of each approach is undertaken. Highlights: There is a paucity of evidence on this topic & overall, the quality is poor. Some of the selected studies contradict each other. The studies affirm the risk of small bowel obstruction if hernias are left alone. SSI rates are low during concomitant bariatric surgery & mesh repair of hernia. A case by case approach is best, with an open discussion of the risks & benefits.